The Rise of Industrial Unions in Montréal 1935-1945 - Copp, Terry (Relations industrielles / Industrial Relations, 1982)
This paper presents a case study of the development of industrial unions in one Canadian city during a crucial union-building decade. It situates the Montréal experience in its provincial, national and continental context.